Pemanfaatan ChatGPT sebagai Media Pembelajaran Teks Biografi dalam Pembelajaran Bahasa Indonesia Kelas X - Sihotang, Aprina Enzel; Hutagalung, Santa Hoky; Surip, M. (Jurnal Bahastra, 2025)
The advancement of artificial intelligence (AI) has significantly transformed the field of education, particularly through the integration of ChatGPT as an interactive learning tool. This study aims to evaluate the effectiveness of ChatGPT in teaching biographical texts to tenth-grade students in Bahasa Indonesia classes. Employing a quantitative approach with a quasi-experimental design, the research involved two groups of students: an experimental group that utilized ChatGPT as a learning medium and a control group that relied on conventional teaching methods. Data were collected through achievement tests, student perception questionnaires, and classroom observations. The findings indicate that the integration of ChatGPT enhanced students’ comprehension of the structure and elements of biographical texts more effectively than traditional methods. Moreover, the students in the experimental group demonstrated higher levels of engagement and interest during the learning process. Therefore, the application of ChatGPT as a pedagogical tool for biographical text instruction offers a promising innovation for improving the quality of Bahasa Indonesia education.